Attachment anxiety and resilience: The mediating role of coping - Ayşe I. Kural (Elsevier, 2021)
In recent research, attachment has been addressed as a core factor that potentially contributes to resilience. However, there is still much to investigate regarding the mechanisms of this relationship. Emotion-focused coping and problem-focused coping strategies may be promising pathways via which attachment associates with resilience. The present study evaluated the role of attachment insecurity (i.e., attachment anxiety and avoidance) in resilience among a Turkish sample during the COVID-19 pandemic. We hypothesized that individuals with high levels of attachment anxiety would experience lower resilience via emotion-focused coping strategies. On the other hand, we did not have a specific hypothesis for attachment avoidance due to contrasting research findings of previous studies. Participants reported their attachment orientation, resilience, and coping strategies. Attachment anxiety was directly and, through both coping strategies, indirectly linked to resilience however attachment avoidance was only indirectly related to resilience through problem-focused coping. The findings indicate that low levels of attachment anxiety and the ability to use problem-focused coping strategies may be associated with greater resilience. The fostering of attachment security may thus reduce the use of emotion-focused strategies and may promote resilience among individuals with high levels of attachment anxiety. Moreover, our study is one of the first to investigate attachment orientations in relevance with coping and resilience during the ongoing pandemic This research has implications regarding the potentials of introducing psycho-educational trainings for better coping strategies in crisis like COVID-19 pandemic.